Detection, transmission and effect of xanthomonas campestris pv. Campestris in the physiological quality of broccoli seeds - Tebaldi, Nilvanira Donizete [UNESP]; De Cássia Panizzi, Rita [UNESP]; Sader, Rubens [UNESP] (My University, 2007)
The detection, transmission and the effect of Xanthomomas campestris pv. campestris (Xcc) in the physiological quality of broccoli seeds were evaluated. The seeds were obtained from inoculated field plants (‘Baron’, ‘Flórida’, ‘Hana Midori Sakata’, ‘Precoce Piracicaba de Verão’, ‘Ramoso Santana’ and ‘Sabre’ genotypes) with the bacterium. For the seed pathogen detection the semi-selective medium were used: Starch for xanthomonads (SX) agar, nutrient starch cycloheximide antibiotic agar (NSCAA) and basal starch cycloheximide antibiotic agar (BSCAA); the bacteria seeds transmission percentage was evaluated using sand and test tube. The physiological seed quality was evaluated by the standard germination and vigor tests: The accelerated aging, speed of emergence, seedling growth and seedling dry weight. The semiselective medium NSCAA was more efficient to detect Xcc from broccoli seeds; there was not significant difference among genotypes regarding the percentage of bacteria transmissed by seeds percentage; although, Xcc can be disseminated by seeds, it did not affect both seed germination and vigor.
Detecção, transmissão e efeito de Xanthomonas campestris pv. Campestris na qualidade fisiológica de sementes de brócolis
Keywords: Black rot; Brassica oleracea var. italica; Seed pathology